Soul Retrieval Following Trauma: A Cultural Comparison. (14th May 2021) - Simington, Jane; Wagner, Joan
Abstract : Post-traumatic Stress Disorder (PTSD) is a disabling psychiatric condition involving an ongoing re-experiencing of the traumatic events. In attempting to escape the distressing emotions involved in the reliving, many PTSD patients with prolonged traumatic experiences, such as childhood abuse and war experiences, show a clinical syndrome that is characterized by dissociation (Lanius, 2010). Spiritual interventions, such as various types of soul retrieval that have been practiced by various First Peoples worldwide, can be effective in addressing the soul loss that occurs as a result of dissociation. This study applied a soul retrieval regression therapy intervention to two different research groups, university students and Indigenous adults, with statistically significant results.